Conceptual design of a fifth generation unmanned strike fighter - Sepulveda, Eduardo; Smith, Howard (AIAA, 2018)
Unmanned aircraft have significantly transformed aerial warfare through a combination of new technologies, extended operational capabilities, and reduced risks and costs. Similarly, computational modelling techniques have accelerated the rate of development for aircraft by being able to explore a large number of design options from the earliest design stages, further reducing time, risks, and costs. The near future will see the proliferation of unmanned combat aerial vehicles under a variety of roles such as unmanned tankers, strike aircraft, and even air - to - air fighters. In this paper the GENUS aircraft design framework is used to develop an unmanned weapons carrying platform able to partially match the performance of 5th generation fighters such as the Joint Strike Fighter F-35A. The vision of future joint operations is for a single lead manned fighter to command and designate targets to its various loyal wingmen unmanned aircraft, extending the combat capabilities and significantly multiplying force and air superiority.